2021
DOI: 10.12998/wjcc.v9.i7.1600
|View full text |Cite
|
Sign up to set email alerts
|

Study on pathogenic genes of dwarfism disease by next-generation sequencing

Abstract: BACKGROUND There are many factors that lead to dwarfism, and the mechanism has not yet been elucidated. Next-generation sequencing may identify candidate-related gene mutations, which may clarify the molecular cause. AIM To analyze genetic variation by using a constructed panel related to dwarfism by utilizing next-generation sequencing platform sequencing analysis to screen candidate-related gene mutations. METHODS Physical and laboratory ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…SLC26A2 is a ubiquitously expressed SO4 2− transporter with high expression levels in cartilage and several epithelia (Ohana et al, 2012;Park et al, 2014). This gene is involved in body size and male fertility in humans (Kujala et al, 2007;Touré, 2019), and its mutations have been implicated in dwarfism (Yang and Liang, 2021) and dysplasia (Pineda et al, 2013;Zheng et al, 2019;Heidari et al, 2021).…”
Section: Identification Of Candidate Genes Associated With High-altit...mentioning
confidence: 99%
See 1 more Smart Citation
“…SLC26A2 is a ubiquitously expressed SO4 2− transporter with high expression levels in cartilage and several epithelia (Ohana et al, 2012;Park et al, 2014). This gene is involved in body size and male fertility in humans (Kujala et al, 2007;Touré, 2019), and its mutations have been implicated in dwarfism (Yang and Liang, 2021) and dysplasia (Pineda et al, 2013;Zheng et al, 2019;Heidari et al, 2021).…”
Section: Identification Of Candidate Genes Associated With High-altit...mentioning
confidence: 99%
“…The function of this gene is related to ion transport, and it plays a role in chondrocyte proliferation, differentiation, and growth in endochondral bone formation (Park et al, 2014). In humans, it regulates body size, and its recessive allele contributes to the dwarfism phenotype (Yang and Liang, 2021) and dysplasia (Pineda et al, 2013;Zheng et al, 2019;Heidari et al, 2021). A previous study reported a dominant allele at SLC26A2 linked to higher heels and stronger claws in dairy cattle, while mutation at the gene causes dysplasia (Brenig et al, 2003).…”
Section: Novel Candidate Gene Identified In This Studymentioning
confidence: 99%